Mitigated Oxidative Stress and Cognitive Impairments in Transient Global Ischemia using Niosomal Selegiline-NBP delivery. (16th April 2022) - Jafari, Bahareh; Gharbavi, Mahmoud; Baghdadchi, Yasamin; Manjili, Hamidreza Kheiri; Mahmoudi, Javad; Jafari-Anarkoli, Iraj; Amiri, Shayan; Hosseini, Mir-Jamal
Abstract : Stroke is the most common reason for adult disabilities and the second ground for death worldwide. Our previous study revealed that selegiline serves as an alternative candidate in transient hypoxia-ischemia. However, aggressive and restless behavior was observed in stroke-induced rats receiving 4 mg/kg selegiline. In comparison, 1 mg/kg selegiline could induce negligible therapeutic effects on mitochondrial dysfunction and histopathological changes. Therefore, we designed oral noisome-based selegiline attached to 4-(4-nitrobenzyl) pyridine to improve transient global ischemia by attenuating cognitive impairments, oxidative stress, and histopathological injury. The investigation was performed in transient hypoxia-ischemia-induced rats by oral administration of nanoformulation containing selegiline (0.25-1 mg/kg) for 4 weeks (3 times a week). Novel object recognition (NOR) was considered to evaluate their cognitive dysfunction. Oxidative stress parameters and brain histopathological assessments were determined following the scarification of rats. Outstandingly, our data demonstrated slower selegiline release from niosomes relative to free drug, which was also in a controlled manner. Our data confirmed significant improvement in cognitive behavior in the NOR test, an increase in glutathione level and total antioxidant power, a decline in MDA and protein carbonyl level, as well as a decreased number of dead cells in histopathological assessment after being exposed to (0.5-1 mg/kg) selegiline-NBP nanoformulation. These data manifested that the selegiline-NBP nanoformulation (0.5-1 mg/kg) could significantly reduce oxidative damage, cognitive dysfunction, and histopathological damage compared to transient hypoxia-ischemia rats, which is 20 times lower than the therapeutic dose in humans. Therefore, the proposed nanoformulation would be capable as an alternative candidate without side effects in stroke.